THE INFLUENCE OF WORKLOAD AND INTELLECTUALS ON THE WORK ETHIC OF PT. MEGA BINTANG MAS MEDAN - Wiriaty Wijaya; Syawaluddin; Aidil Putra; Thomas Sumarsan Goh (Universitas Putera Batam, 2022)
This research was conducted on employees who work at PT. Mega Bintang Mas Medan. The purpose of this study was to determine and analyze the influence of workload and intellectuality on the work ethic of employees. The population and sample in this study amounted to 31 people. The sampling technique used is saturated. Data collection techniques are by distributing questionnaires and interviews. Data analysis used multiple linear regression analysis. The conclusion in the study that simultaneously workload and intellectual have a positive and significant effect on the work ethic of employees of PT. Mega Bintang Mas Medan. Partially, the workload affects the work ethic of the employees of PT. Mega Bintang Mas Medan. Partially, intellectuals do not have a positive and significant effect on the work ethic of the employees of PT. Mega Bintang Mas Medan. The magnitude of the coefficient of determination can be seen from the value of Adjusted R Square is: 0.330 means Workload and Intellectuals are able to explain the work ethic of employees by 33.0% while the remaining 67.0% is influenced by variables not examined such as: organizational culture, work environment, motivation work, and so on.